ANALISIS KEMAMPUAN 4C’s SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERPIKIR TINGKAT TINGGI - Asviangga, Aji Bagoes; Sunardi, S; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2018)
Abstract This research analises students of 4C on solve mathematic thinking problem high-level, with purpose to describe competence of 4C’s students of MTsN Satu Atap class VIII on solve mathematic thinking problem high-level. Researcher chooses one group from five groups which is every group has five members. The chosen group is a subject of research. Collecting data uses two methods which are test and interview method. The result of this research shows that student 4C’s skill have been in three indicators, those are communication, creative thinking, and collaboration skill, whereas critical thinking isn’t had by students. Keywords: 4C’s Skill, High Order Thinking